Evaluation of diagnostic utility of multidetector computed tomography and magnetic resonance imaging in blunt pancreatic trauma: a prospective study. (April 2015) - Panda, Ananya; Kumar, Atin; Gamanagatti, Shivanand; Bhalla, Ashu Seith; Sharma, Raju; Kumar, Subodh; Mishra, Biplab
Background: Blunt pancreatic trauma is an uncommon injury with high morbidity and mortality. Retrospective analyses of computed tomography (CT) performance report CT to have variable sensitivity in diagnosing pancreatic injury. Both a prospective analysis of multidetector CT (MDCT) performance and diagnostic utility of magnetic resonance imaging (MRI) in acute blunt pancreatic injury remain unexplored. Purpose: To prospectively evaluate the utility of MDCT with MRI correlation in patients with blunt pancreatic trauma using intraoperative findings as the gold standard for analysis. Material and Methods: The contrast-enhanced CT (CECT) scans of patients admitted with blunt abdominal trauma were prospectively evaluated for CT signs of pancreatic injury. Patients detected to have pancreatic injury on CT were assigned a CT grade of injury according to American Association for Surgery of Trauma classification. MRI was performed in patients not undergoing immediate laparotomy and MRI grade independent of CT grade was assigned. Surgical grade was taken as gold standard and accuracy of CT and MRI for grading pancreatic injury and pancreatic ductal injury (PDI) was calculated. A quantitative and qualitative comparison of MRI was also done with CT to determine the performance of MRI in acute pancreatic injury. Results: Thirty out of 1198 patients with blunt trauma abdomen were detected to have pancreatic injury on CT, which was surgically confirmed in 24 patients. Seventeen underwent MRI and surgical correlation was available in 14 patients. CT and MRI correctly identified the grade of pancreatic injury in 91.7% (22/24) and 92.86% (13/14) patients, respectively. Both CT and MRI correctly identified PDI in 18/19 and 11/12 patients, respectively, with good inter-modality agreement of 88.9% (kappa value of 0.78). MRI also qualitatively added to the information provided by CT and increased diagnostic confidence in 58.8% of patients. Conclusion: MDCT performs well in grading pancreatic injury and evaluating pancreatic ductal injury. MRI is useful in evaluation of acute pancreatic trauma as it can increase diagnostic confidence and provide more qualitative information regarding the extent of injury.